ANALISIS IMPLEMENTASI KEBIJAKAN MANAJEMEN BERBASIS SEKOLAH PADA MADRASAH ALIYAH DI KABUPATEN LUWU UTARA - Muh Takdir; Muhammad Yusuf; Alimuddin Alimuddin (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The objective of research is to analyze and to describe the implementation of School-Based Management (MBS) policy, the factors supporting and constraining the implementation of MBS policy, and the response of teachers to the implementation of MBS policy at Madrasah Aliyah in Luwu Utara District. The precise location of research is at MA Muhammadiyah Balebo, MA Al-Falah Lemahabang and MAN Luwu Utara. Research design is qualitative with descriptive method analysis through Edward III theory. Data collection techniques involve interview, observation and documentation. Data are subjected to the analysis which involves data reduction, data presentation, and verification/conclusion. The conclusion is managerial competence of principal and active participation of whole stakeholders, especially community with their moral and material supports based on demand of madrasah, are main factors to implement MBS policy.